Return to the little coffee shop of Kabul - Rodriguez, Deborah (Sphere, 2016)
Six women forever joined by a little cafe in Kabul Sunny, former proprietor of the Little Coffee Shop and new owner of the Screaming Peacock vineyard. Can she handle the challenges of life on her own? Yasmina, the young mother who now runs the cafe, until a terrifying event strikes at the heart of her family and business ... Layla and Kat Afghan teenagers in America, struggling to make sense of their place in the world ... Zara, about to be forced into a marriage which will have devastating consequences ... These women are about to learn what Halajan, Yazmina's rebellious mother-in-law, has known all along: when the world as you know it disappears, you find a new way to live.